2020
DOI: 10.3390/brainsci10110768
|View full text |Cite
|
Sign up to set email alerts
|

POLG1-Related Epilepsy: Review of Diagnostic and Therapeutic Findings

Abstract: Background: The clinical spectrum associated with POLG1 gene mutations ranges from non-syndromic epilepsy or mild isolated neurological signs to neurodegenerative disorders. Our aim was to review diagnostic findings, therapeutic approaches and outcomes of reported cases of epilepsy related to POLG1 mutation. Methods: The articles for review were identified through a systematic research on PubMed and EMBASE databases from January 2003 to April 2020, searching for the terms “Epilepsy AND POLG OR polymerase gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
2
4
0
Order By: Relevance
“…In a series of 19 patients with POLG1, occipital rhythmic slowing was present in 7 patients and occipital interictal discharges was present in 18 patients, demonstrating an occipital predilection in POLG ( 15 ). This finding, as seen in our study over the disease course, is concordant with electrophysiologic data reported by other authors ( 10 , 16 , 28 , 29 ). Occipital status epilepticus and occipital seizures have also been previously reported in MELAS; this manifestation may precede other clinical signs of the disease and serve as a potential diagnostic clue ( 29 , 32 , 33 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In a series of 19 patients with POLG1, occipital rhythmic slowing was present in 7 patients and occipital interictal discharges was present in 18 patients, demonstrating an occipital predilection in POLG ( 15 ). This finding, as seen in our study over the disease course, is concordant with electrophysiologic data reported by other authors ( 10 , 16 , 28 , 29 ). Occipital status epilepticus and occipital seizures have also been previously reported in MELAS; this manifestation may precede other clinical signs of the disease and serve as a potential diagnostic clue ( 29 , 32 , 33 ).…”
Section: Discussionsupporting
confidence: 94%
“…Our findings are supported by previous patient series and literature reviews on epilepsy features in mitochondrial disorders (Table 3) (8,10,16,(28)(29)(30)(31). Focal seizures were the predominant seizure type in our series, which is in agreement with the previous review by Anagnostou et al in POLG and a recent case series in MELAS by Li et al (10,28).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) of the brain often demonstrates T2 and FLAIR hyperintensities in the cortical and subcortical regions, particularly in the occipital lobes. Similar lesions are also seen in the thalamus and cerebellum [ 33 ]. Electroencephalography (EEG) findings are variable but occipital discharges and slowing are frequently seen, as are rhythmic high-amplitude delta with superimposed spikes (RHADS) [ 33 ].…”
Section: Introductionmentioning
confidence: 73%
“…Myoclonus is the most common presented seizure type and patients often develop status epilepticus or epilepsy partialis continua. The seizures become refractory to treatment and worsen prognosis [ 33 ]. Valproic acid is contraindicated as it can precipitate or accelerate liver failure by inhibition of fatty acid beta-oxidation which impairs mitochondrial function [ 11 , 12 , 15 , 26 ].…”
Section: Introductionmentioning
confidence: 99%